Genova bankers and merchants in the Spanish Habsburg Empire in the first half of the sixteenth century - Mohsen, Faten Mohi (Al-Adab Journal, 2022)
This study discusses the political and commercial relations between Genoa money-changers and merchants and the Spanish monarchy of the Habsburgs in the first half of the sixteenth century, as Genoa represented a model of the city-state from an institutional perspective and a Spanish protectorate within the framework of the study of international relations, and to shed light on the development of these relations and their impact on Achieving relative political stability and strong economic growth for both parties, as well as studying the controversial fluctuations that Italy witnessed during that decisive period in which Italy was squeezed into the sphere of influence of the Spanish monarchy. Commercial projects and their exits are profitable despite the limited possibilities of state-building (a small regional state whose population does not exceed 250 thousand and its lands are not fertile and do not have military forces). On this basis, the research studies the role of Genoa exchanges in the finances of the Spanish Kingdom and the political and commercial relations between Genoa, Spain and France in the first half of the sixteenth century, it then deals with the economic construction between Genoa and the Spanish Habsburg imperial regime.